2010
DOI: 10.5380/rsa.v11i6.20395
|View full text |Cite
|
Sign up to set email alerts
|

ESTAQUIA SEMILENHOSA DE Vochysia bifalcata

Abstract: O objetivo desse trabalho foi verificar o enraizamento de estacas semilenhosas de Vochysia bifalcata (guaricica). As estacas foram preparadas com 12 ± 2 cm de comprimento, 0,3 a 0,6 mm de diâmetro e duas folhas na porção apical com sua área reduzida à metade. Foi utilizado o delineamento experimental inteiramente casualizado, com quatro repetições, em esquema fatorial 4 x 2 (quatro concentrações de AIB: zero, 500, 1000 e 2000 mg dm-3; e com ou sem aplicação de antioxidante PVP40). Cada unidade experimental foi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Similar results were obtained from other species subjected to reinvigoration methods aiming at the cuttings vegetative propagation. Vochysia bifalcata (Vochysiaceae) when subjected to conventional cutting, with the collection of propagules directly from the source plant, did not present rooting (Danner et al, 2010), however, when the species was subjected to reinvigoration methods, such as drastic pruning, 81.0% of rooting was obtained (Rickli et al, 2015). Bitencourt et al (2009) comparing two types of cuttings (cuttings from annual sproutings and cuttings from re-sproutings) of the Yerba Mate, showed that the material reinvigorated by pruning presented higher percentages of rooting (65.5%) in relation to the one from annual sprouings (8.5%).…”
Section: Resultsmentioning
confidence: 99%
“…Similar results were obtained from other species subjected to reinvigoration methods aiming at the cuttings vegetative propagation. Vochysia bifalcata (Vochysiaceae) when subjected to conventional cutting, with the collection of propagules directly from the source plant, did not present rooting (Danner et al, 2010), however, when the species was subjected to reinvigoration methods, such as drastic pruning, 81.0% of rooting was obtained (Rickli et al, 2015). Bitencourt et al (2009) comparing two types of cuttings (cuttings from annual sproutings and cuttings from re-sproutings) of the Yerba Mate, showed that the material reinvigorated by pruning presented higher percentages of rooting (65.5%) in relation to the one from annual sprouings (8.5%).…”
Section: Resultsmentioning
confidence: 99%
“…Neste sentido, Fragoso et al (2015) relatam que a presença de folhas foi indispensável para o enraizamento de estacas de Prunus serrulata Lindl. No estudo desenvolvido por Danner et al (2010) os resultados demonstraram que a baixa porcentagem de manutenção de folhas prejudicou o enraizamento e aumentou a mortalidade das estacas de Vochysia bifalcata Warm.…”
Section: Discussionunclassified